Ocular Dominance and Handedness in Golf Putting. Issue 10 (October 2015) - Dalton, Kristine; Guillon, Michel; Naroo, Shehzad A.
ABSTRACT: Purpose: In golf, the impact of eye-hand dominance on putting performance has long been debated. Eye-hand dominance is thought to impact how golfers judge the alignment of the ball with the target and the club with the ball, as well as how golfers visualize the line of the putt when making decisions about the force needed to hit the ball. Previous studies have all measured ocular dominance in primary gaze only, despite golfers spending a significant amount of their time in a putting stance (bent at the hips, head tilted down). Thus, the purpose of this study was to assess ocular dominance in both primary gaze (aligning the ball with the target) and putting gaze (addressing the ball and aligning the club). Methods: This study investigated measuring pointing ocular dominance in both primary and putting gaze positions on 31 golfers (14 amateur, 7 club professionals, and 10 top professionals). All players were right-handed golfers, although one reported having no hand dominance and one reported being strongly left hand dominant. Results: The results showed that (1) primary and putting gaze ocular dominances are not equal, nor are they predictive of each other; (2) the magnitude of putting ocular dominance is significantly less than the magnitude of primary gaze ocular dominance; (3) ocular dominance is not correlated with handedness in either primary or putting gaze; and (4) eye-hand dominance is not associated with increased putting skill, although ocular dominance may be associated with increased putting success. Conclusions: It is important that coaches assess golfers' ocular dominance in both primary and putting gaze positions to ensure they have the most accurate information upon which to base their vision strategy decisions. Abstract : Supplemental digital content is available in the text.